2019
DOI: 10.1371/journal.pone.0223538
|View full text |Cite
|
Sign up to set email alerts
|

Weather extremes and perinatal mortality – Seasonal and ethnic differences in northern Sweden, 1800-1895

Abstract: BackgroundMany studies have shown the impact of heat and cold on total and age-specific mortality, but knowledge gaps remain regarding weather vulnerability of very young infants. This study assessed the association of temperature extremes with perinatal mortality (stillbirths and deaths in the first week of life), among two ethnic groups in pre-industrial northern Sweden.MethodsWe used population data of indigenous Sami and non-Sami in selected parishes of northern Sweden, 1800–1895, and monthly temperature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…In this paper, we studied the association of daily temperature and seasonality with neonatal mortality, covering a sensitive period of an infant's life. Our previous studies, based on monthly mean temperatures, showed that Sami perinatal and neonatal mortality were influenced by extreme cold in the winter, whereas extreme cold winter temperature had no effect on the non-Sami population [6,8].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this paper, we studied the association of daily temperature and seasonality with neonatal mortality, covering a sensitive period of an infant's life. Our previous studies, based on monthly mean temperatures, showed that Sami perinatal and neonatal mortality were influenced by extreme cold in the winter, whereas extreme cold winter temperature had no effect on the non-Sami population [6,8].…”
Section: Introductionmentioning
confidence: 91%
“…Based on information about family name, parish, occupation and family relations, an ethnical indicator that distinguished between the Sami population and the non-Sami population has been developed [39]. This ethnical indictor has been used in a variety of studies regarding marriage, fertility and mortality patterns in Swedish Sápmi [4,[6][7][8]13,23,39,40]. The available information about ethnicity does not allow a differentiation between nomadic and settled Sami.…”
Section: Population Datamentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous findings regarding the effect of temperature on neonatal health in sub-Arctic areas (Karlsson et al, 2020;Schumann et al, 2019), we expected a strong impact of low temperatures, especially among more resource-poor groups (farmers and workers) that would diminish over time. A declining effect was not clearly discernible in any social group due to the low vulnerability observed in the first decades of the twentieth century.…”
Section: Discussionmentioning
confidence: 80%
“…It was uncertain what explain the current results although there were several factors which might be important. Firstly, several researches reported that winter was a high-risk time, perinatal and neonatal mortality was influenced by extreme cold in winter [ 20 , 21 ], and January is the coldest month of winter in China. Secondly, many studies have demonstrated a link between early life nutrition and cardiovascular health and mortality in adulthood [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%